Africa’s Development and Post Covid-19 Emerging Opportunities: Towards a Political Economic Model for Strengthening Intra Africa Trade and National/Regional Competitiveness in Response to Global Supply Chain Disruption - Oladele, Aderemi; Vieyra-Mifsud, Olola (Technium Social Sciences Journal, 2021)
In view of the general observation that emerging opportunities exist for developing economies in the aftermath of the COVID-19 global pandemic, despite its many health, safety, economic, social and environmental realities, this paper examines how Africa could translate the challenges of the crisis into positive development opportunities from three interrelated salient angles: first is how to consolidate on innovation for local production and reinforce intra-African trade; the second is strengthening innovation for more resilient policies that address youth employment and skills development for regional and global competitiveness; and third, refocusing the digital and green economies, including the strengths of artificial intelligence, big data, e-commerce and the continuity of related environmental objectives. Using the “systems approach”, it proposes three quaternal models, advocating for policy coherence as optimal for development deliverables. This is not only beneficial for helping Africa out of the crisis, but could also meet some novel and future-oriented objectives of capacity building for managing complexities as purported in current global and regional development Agendas 2030 and 2063, as well as the African Continental Free Trade Area (AfCFTA) proposals.